Pembelajaran Pola Bilangan di SMP: Sebuah Aktivitas Lesson Study Berbasis Didactical Design Research - Isnawan, Muhamad Galang; Alsulami, Naif Mastoor; Bonyah, Ebenezer; Dejarlo, Jenisus O.; Sudirman, Sudirman (Edumatica : Jurnal Pendidikan Matematika, 2024)
Number patterns were one of the mathematical concepts that were studied in junior high school. This concept was useful, but students tended to experience problems when learning it. Quite a lot of research has studied number patterns, but not many have attempted to study alternative solutions to optimize problem-solving abilities and learning motivation, especially using lesson study activities based on didactical design research. Therefore, this research aimed to optimize students’ problem-solving abilities and learning motivation with the preparation of didactic designs through lesson study activities. This research was conducted at a private junior high school in Mataram, Indonesia. Participants in this research were ten class VIII students (six boys and four girls). The researcher was the main instrument, with several additional instruments, such as learning design, observation sheets on problem-solving abilities and learning motivation, as well as documentation studies. The data were analyzed using qualitative data analysis. The research results revealed that the number pattern learning design was able to optimize problem-solving abilities and student learning motivation. Several factors that caused these positive results were the existence of contextual problems as trigger situations in learning and learning activities adapted to students’ hobbies. The recommendation from this research was that learning design should be prepared using didactical design research based on lesson study.